Role of work motivation in moderate the influence of satisfaction employee work and organizational commitmenton employee performance - Norawati, Suarni; Mar'i, Sulaeman (Institute of Computer Science (IOCS), 2024)
State Electric Company PT (Persero) is an Indonesian state-owned company which operates in the electricity sector. In providing the best service to customers, good performance from employees is very necessary, therefore it is necessary to pay attention to the factors that influence employee performance. The aim of this research is to determine and analyze 1) the influence of job satisfaction on employee performance; 2) the influence of organizational commitment on employee performance; 3) the influence of work motivation on employee performance; 4) the influence of job satisfaction on employee performance which is mediated by work motivation; and 5) the influence of organizational commitment on employee performance which is mediated by work motivation. The research was conducted at PT PLN (Persero) Pekanbaru Area, the research data used was primary data and secondary data obtained using questionnaires, research files. The sample for this research was 127 employees, and data analysis was carried out using the SEM (Structural Equation Modling) model and in data processing the SmartPLS program was used, hypothesis testing was carried out at an alpha of 5%. The results of this research conclude that 1) job satisfaction has been proven to have a significant effect on employee performance; 2) organizational commitment is proven to have a significant effect on employee performance, 3) work motivation is proven to have a significant effect on employee performance; 4) it is proven that there is an influence of job satisfaction on employee performance which is mediated by work motivation; and 5) it is proven that there is an influence of organizational commitment on employee performance which is mediated by work motivation.